Espectro de biomassa de peixes e a influência de fatores físicos e limnológicos em áreas litorâneas de reservatórios neotropicais - Santos, Vinicius Valiente dos (2011)
The size spectrum associates the abundance of individuals with the body size of these. The aim of this study was to identify the spectra of biomass of reservoirs coastal áreas and investigate the influence of physical and limnological factors on the distribution of individuals in different biomass classes. Samples were collected quarterly in 13 neotropical reservoirs in southern Brazil. To evaluate the spectra size of the ichthyofauna assemblies, the frequencies were determined by classes of individuals logarithmic on base 2 of biomass and transformed, and these were submitted to correspondence analysis. The effects of physical and limnological factors on biomass spectra were evaluated by their correlations with the axés generated of correspondence analysis. Correspondence analysis (CA) concentrated 93% of the total inertia in the first axis. In this axis, the largest contributions were from the accumulated frequency of individuals weighing up to 8g and 16g, leaving low variability in subsequent classes. Some reservoirs had high proportion of small individuals (<16g), while others had small proportion, with tanks to Salto Caxias and Guaricana rerservoirs, respectively, at the extremes of this gradient. The physical and limnological factors correlated with the first axis of correspondence analysis showed association with altitude, water temperature and dissolved oxygen. The results showed a predominance of smaller classes of biomass(<16g) in the coastal regions of the reservoirs, and the temperature was the main factor in the size spectra of fish assemblages.